2016
DOI: 10.1038/srep27885
|View full text |Cite
|
Sign up to set email alerts
|

A comparative genomic analysis of targets of Hox protein Ultrabithorax amongst distant insect species

Abstract: In the fruitfly Drosophila melanogaster, the differential development of wing and haltere is dependent on the function of the Hox protein Ultrabithorax (Ubx). Here we compare Ubx-mediated regulation of wing patterning genes between the honeybee, Apis mellifera, the silkmoth, Bombyx mori and Drosophila. Orthologues of Ubx are expressed in the third thoracic segment of Apis and Bombyx, although they make functional hindwings. When over-expressed in transgenic Drosophila, Ubx derived from Apis or Bombyx could sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 39 publications
7
42
0
1
Order By: Relevance
“…Here we used the phycitine Indian Mealmoth (P. interpunctella) as a model system to investigate additional aspects of lepidopteran wing specialization. First, we confirmed that the UbdA antigen (anti-Ubx/abd-A FP6.87 monoclonal antibody) is absent from the forewing imaginal disks, and expressed throughout the hindwing, thus corroborating the hindwing-specific expression of Ubx described in other lepidopterans (Weatherbee et al, 1998;Tong et al, 2014;Prasad et al, 2016). Then, we generated Ubx mosaic knock-outs and observed homeotic clones on the hindwing that were most conspicuous as transpositions toward black-andbrown pigmented states on the dorsal side ( Figures 6A,B and Supplementary Figure 6).…”
Section: Ubx Permits the Morphological Specialization Of Pyralid Hindsupporting
confidence: 80%
“…Here we used the phycitine Indian Mealmoth (P. interpunctella) as a model system to investigate additional aspects of lepidopteran wing specialization. First, we confirmed that the UbdA antigen (anti-Ubx/abd-A FP6.87 monoclonal antibody) is absent from the forewing imaginal disks, and expressed throughout the hindwing, thus corroborating the hindwing-specific expression of Ubx described in other lepidopterans (Weatherbee et al, 1998;Tong et al, 2014;Prasad et al, 2016). Then, we generated Ubx mosaic knock-outs and observed homeotic clones on the hindwing that were most conspicuous as transpositions toward black-andbrown pigmented states on the dorsal side ( Figures 6A,B and Supplementary Figure 6).…”
Section: Ubx Permits the Morphological Specialization Of Pyralid Hindsupporting
confidence: 80%
“…( e ) Browser representation of the slit locus. Silk gland FAIRE, from top to bottom: silk gland FAIRE peaks, BmE FAIRE peaks, and Ubx chip peaks 47 . …”
Section: Resultsmentioning
confidence: 99%
“…For example, enhancers of some developmental genes in beetles, honeybees and even spiders were demonstrated to be active in their expected contexts in Drosophila (e.g. Ayyar et al, 2010;Cande et al, 2009a,b;Kazemian et al, 2014;Lai et al, 2018;Prasad et al, 2016;Wolff et al, 1998;Zinzen et al, 2006). These studies show the power of the cross-species reporter assay using Drosophila as an in vivo test tube, but with one unavoidable concern: are these non-Drosophila enhancers really showing biologically relevant activities in Drosophila?…”
Section: Testing Activity Of Non-drosophila Enhancers In Drosophilamentioning
confidence: 99%